The Effectiveness of the Training of Problem-Solving and Decision-Making Skills on the Reduction of Addicts' Positive Attitudes to Narcotics - Farxaneh Bahrami; Ameneh Moazedian; S Ali Hosseini (Drug Control Headquarters, Research and Education Office, 2013)
Aim: The purpose of this study was to examine the effect of the training of problem-solving and decision-making skills on the reduction of addicts' positive attitudes to narcotics. Method: The design of this study was experimental design namely: pre and post test with control group. The population included all addicts referring to Sanandaj self-report centers (500 addicts). By random sampling, 60 addicts were selected and completed the attitude questionnaire to narcotics use. Each of experimental groups was under problem-solving and decision-making skills training for ten 90 minute sessions. No training given to control group. Results: After training, two experimental groups significantly had lower levels of positive attitude to narcotics use. No difference was observed between two experimental groups. Conclusion: The results of this study indicated that the training of problem-solving and decision-making skills can reduce the addicts' positive attitudes to narcotics.